COMPARATIVE STUDY OF THE FUNCTIONAL SEMANTIC FIELD IN ENGLISH AND UZBEK LANGUAGES - Ataboev, Isroil; Rustamov, Ilhom; Rustamova, Shaxnoza; Mallaeva, Ozoda (Журнал иностранных языков и лингвистики, 2021)
This Article is about comparative study of the functional semantic field in English and Uzbek languages.